Synthesis and Characterization of Photoelectrocatalytic Electrodes for Methylene Blue Degradation - Oh, Won-Chun; Kim, Jong-Gyu; Kim, Hyuk; Park, Chong-Yeon; Zhu, Lei; Ullah, Kefayat; Ye, Shu; Meng, Ze-Da (Asian Journal of Chemistry, 2013)
In this study, series of electrodes were prepared. The decrease of surface area compared with that of the pristine activated carbon indicated the blocking of micropores on the surface of the activated carbons; was further supported by scanning electron microscopy. The X-ray diffraction results showed that the composites contained a mixture of anatase forms of TiO2 particles when the precursor was TiO2 powder, whereas when the precursor was TOS, the composites contained only the typical single and clear anatase TiO2 particles. The energy dispersive X-ray spectroscopy showed the presence of C, O and Ti peaks for all samples. It was found that catalytic decomposition of methylene blue solution could be attributed to synthetic effects between the TiO2 photocatalysis and electro-assisted ACs network and that photoelectrocatalytic oxidation increased with added of Co and graphene composition.